WHAT IS THE ROLE OF THE GOVERNMENT IN MONITORING SUGAR CONTENT IN FOOD TO MAINTAIN HEALTH - Vicki Dwi Purnomo; sigit irianto; sri mulyani (CV. RADJA PUBLIKA, 2024)
Excessive sugar consumption in children has become an increasingly worrying public health issue, especially due to the increased risk of obesity, type 2 diabetes and other diseases. The government has an important role in monitoring and controlling the sugar content in food consumed by children through various policies and regulations. This paper examines the role of the Indonesian government in monitoring sugar content in children's food, including the policies that have been implemented, the challenges faced, and evaluating the effectiveness of these policies. The results of the study show that although measures such as sugar content labeling and education campaigns have been implemented, the effectiveness of these policies is still limited by various factors, such as food industry resistance, low public awareness, and limited supervision. Based on policy analysis in other countries, such as the UK and Mexico, it is recommended that the Indonesian government consider implementing additional policies, such as a sugar tax, as well as strengthening public education and monitoring existing regulations. In conclusion, the government's role in monitoring sugar content in children's food is very important, however still needs strengthening and improvement so that the goal of protecting children's health can be achieved effectively.